Comparison of Early Versus Delayed Oral Feeding after Resection and Anastomosis of Gut - Siddiqi, Ubaid Ullah; Nasir, Ammad Ud Din; Ilyas, Sohail; Sarfraz, Khurram; Farooq, Muhammad Omar; Rehman, Shafqat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the outcomes of early versus delayed postoperative oral feeding in patients undergoing resection and anastomosis of the gut.Study Design: Quasi-experimental studyPlace and Duration of Study: Surgical Department of Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jun 2020 to May 2021.Methodology: A total of 30 patients fulfilling the selection criteria were enrolled after taking written informed consent and were randomly divided into two groups of equal numbers. Patients in Group-A received early oral feeding, and in Group-B had delayed oral feeding postoperatively, and the outcome measures were assessed till the patients were discharged.Results: The mean duration of hospital stay in Group-A versus Group-B was 50.94 days vs. 60.74 days (p=0.005), the mean time to passage of the first flatus was 30.61 days vs. 50.48 days (p